Cannabis use characteristics and associations with problematic use outcomes, quitting-related factors, and mental health among US young adults - Carla J. Berg; Cassidy R. LoParco; Katelyn F. Romm; Yuxian Cui; Darcey M. McCready; Yan Wang; Y. Tony Yang; Hannah S. Szlyk; Erin Kasson; Rishika Chakraborty; Patricia A. Cavazos-Rehg (Substance Abuse Treatment, Prevention, and Policy)
Abstract Objective Given the changes in trends of cannabis use (e.g., product types), this study examined latent classes of young adult use and associations with use-related outcomes. Methods We analyzed 2023 survey data among 4,031 US young adults (Mage=26.29, 59.4% female, 19.0% Hispanic, 13.5% Black, 13.6% Asian). Among those reporting past-month use (48.8%), latent class analysis (LCA) indicators included: days used (1–5; 6–20; 21–30), use/day (1; 2–4; ≥5), and type usually used (herb/flower; edibles; oils/vape; concentrates/other). Multivariable regressions examined class in relation to problematic use, quitting-related factors, and mental health, controlling for sociodemographics and state non-medical cannabis laws. Results LCA identified 4 classes of cannabis use frequency and types used: ‘infrequent-herb/edibles’ (41.4%), ‘frequent-herb’ (16.8%), ‘moderate-herb’ (28.0%), and ‘moderate-oil/other’ (13.8%). In multivariable analyses (referent group: ‘moderate-herb’ class), ‘frequent-herb’ reported less problematic use (B=-0.18, 95%CI=-0.30, -0.07), while ‘moderate-oil/other’ reported greater (B = 0.39, 95%CI = 0.27, 0.51). ‘Infrequent-herb/edibles’ had lower odds of driving post-use of cannabis (aOR = 0.28, 95%CI = 0.22, 0.37) and cannabis/alcohol (aOR = 0.52, 95%CI = 0.35, 0.76), whereas ‘frequent-herb’ (aOR = 1.52, 95%CI = 1.02, 2.28) and ‘moderate-oil/other’ (aOR = 3.98, 95%CI = 2.72, 5.82) reported greater odds of driving post-cannabis/alcohol use. ‘Moderate-oil/other’ reported higher quitting importance (B = 0.59, 95%CI = 0.17, 1.01), while ‘frequent-herb’ reported lower (B=-0.33, 95%CI=-0.99, -0.18). ‘Infrequent-herb/edibles’ reported higher quitting confidence (B = 0.56, 95%CI = 0.20, 0.92), whereas ‘frequent-herb’ (B=-1.01, 95%CI=-1.45, -0.57) and ‘moderate-oil/other’ (B=-1.27, 95%CI=-1.74, -0.81) reported lower. ‘Infrequent-herb/edibles’ reported fewer mental health symptoms (B=-0.55, 95%CI=-0.93, -0.17), while ‘moderate-oil/other’ reported more (B = 1.03, 95%CI = 0.53, 1.52). Conclusions Preventing frequent and moderate use of cannabis, particularly of oils/concentrates, is crucial given the potential negative implications for problematic use, quitting, and mental health.